Pengaruh Kualitas Produk, Garansi, dan Teman Sebaya Terhadap Minat Beli Produk Motor Honda Dengan Rangka eSAF - Georano Indriyanto; Rini Anggriani; L. Jatmiko Jati; M. Chotibul Umam Assa’ady; Stevany Hanalyna Dethan (CV. ITTC INDONESIA, 2025)
The purpose of this study is to determine the influence of product quality, warranty, and peer influence on the purchase intention of Honda motorcycles with eSAF frames in Mataram City. This study is a quantitative study. The researcher set the sample size at 100 respondents who are members of the Honda motorcycle community with eSAF frames. This study focuses on the issue of Honda motorcycles allegedly being prone to rust and breakage. The novelty of this study lies in the peer influence variable, as peer influence is rarely studied in relation to purchase intent. Data analysis was conducted using SPSS 23. The results found that product quality influences purchase intent. Warranty does not influence purchase intent. Peer influence influence purchasing intent. Product quality, warranty, and peers simultaneously influence purchasing intent. Based on the results of the multiple linear regression test, product quality has a positive and significant influence on purchasing intent. Warranty has a negative and insignificant influence on purchasing intent. Peers have a positive and significant on purchase intention. Product quality, warranty, and peers have a positive and significant simultaneous effect on purchase intention.